Content and tissue expression of Collagen I, Collagen IV, and Laminin in the Extracellular Matrix in Prostate Adenocarcinoma - Igor Arantes Góes; Maria Roberta Martins Pereira; Enrico Crotti; Geovanna Paciulli Pereira; Mateus Magami Yoshitani; Marcos Antonio Castro; Jose Aires Pereira; Carlos Augusto Real Martinez (Journal of Molecular Histology, 2024)

Evaluation of the in vitro schistosomicidal, leishmanicidal, and trypanocidal activities of the capsaicin metabolite, Capsicum frutescens , and Capsicum baccatum extracts and of their analysis of the main constituents by HPLC/UV and CG/MS - Sandra Vaz Soares Martins; Angélica Cristina Coelho Britto; Marcos Gomide Tozzati; Lizandra Guidi Magalhães; Márcio Luis Andrade e Silva; Ana Helena Januário; Patrícia Mendonça Pauletti; Antônio Eduardo Miller Crotti; Amanda Vargas dos Passos; Ester Gonçalves de Jesus; Amanda Diniz Peixoto; Gabriela dos Santos Medeiros; et al. (Natural Product Research, 2024)

The role of Mycoplasma ovipneumoniae and Mycoplasma arginini in the respiratory mycoplasmosis of sheep and goats in Italy: Correlation of molecular data with histopathological features - Silvia Pavone; Silvia Crotti; Nicoletta D'Avino; Paola Gobbi; Eleonora Scoccia; Cristina Pesca; Marco Gobbi; Valentina Cambiotti; Elvio Lepri; Deborah Cruciani (Research in Veterinary Science, 2023)

The Thorny Issue of African Porcupines: a New Mandible of Hystrix makapanensis from Olduvai Gorge (Tanzania) and Rediagnosis of the Species - Beatrice Azzarà; Marco Cherin; Justin Adams; Giovanni Boschian; Marco Crotti; Christiane Denys; Lorenzo Fressoia; Jackson S. Kimambo; Amandus Kwekason; Dawid A. Iurino; Giorgio Manzi; Fidelis T. Masao; et al. (Journal of Mammalian Evolution, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Developmental stages and gut microenvironments influence gut microbiota dynamics in the invasive beetle Popillia japonica Newman (Coleoptera: Scarabaeidae) - Bessem Chouaia; Nizar Goda; Giuseppe Mazza; Sumer Alali; Fiorella Florian; Fabrizia Gionechetti; Matteo Callegari; Elena Gonella; Giulia Magoga; Marco Fusi; Elena Crotti; Daniele Daffonchio; et al. (Environmental Microbiology, 2019)
Summary Popillia japonica Newman (Coleoptera: Scarabaeidae) is a highly polyphagous invasive beetle originating from Japan. This insect is highly resilient and able to rapidly adapt to new vegetation. Insect‐associated microorganisms can play important roles in insect physiology, helping their hosts to adapt to changing conditions and potentially contributing to an insect's invasive potential. Such symbiotic bacteria can be part of a core microbiota that is stably transmitted throughout the host's life cycle or selectively recruited from the environment at each developmental stage. The aim of this study was to investigate the origin, stability and turnover of the bacterial communities associated with an invasive population of P. japonica from Italy. Our results demonstrate that soil microbes represent an important source of gut bacteria for P. japonica larvae, but as the insect develops, its gut microbiota richness and diversity decreased substantially, paralleled by changes in community composition. Notably, only 16.75% of the soil bacteria present in larvae are maintained until the adult stage. We further identified the micro‐environments of different gut sections as an important factor shaping microbiota composition in this species, likely due to differences in pH, oxygen availability and redox potential. In addition, P. japonica also harboured a stable bacterial community across all developmental stages, consisting of taxa well known for the degradation of plant material, namely the families Ruminococcacae, Christensenellaceae and Lachnospiraceae. Interestingly, the family Christensenallaceae had so far been observed exclusively in humans. However, the Christensenellaceae operational taxonomic units found in P. japonica belong to different taxonomic clades within this family.

Differential selection pressures result in a rapid divergence of donor and refuge populations of a high conservation value freshwater fish Coregonus lavaretus (L.) - J. Peter Koene; Marco Crotti; Kathryn R. Elmer; Colin E. Adams (Evolutionary Ecology, 2019)

Electrolytic Recovery of Nickel and Copper from Acid Pickling Solutions Used to Treat Metal Surfaces - Maria Cristina Collivignarelli; Alessandro Abbà; Massimiliano Bestetti; Barbara Marianna Crotti; Marco Carnevale Miino (Water, Air, & Soil Pollution, 2019)

Causes and analytical impacts of missing data in RADseq phylogenetics: Insights from an African frog ( Afrixalus ) - Marco Crotti; Christopher D. Barratt; Simon P. Loader; David J. Gower; Jeffrey W. Streicher (Zoologica Scripta, 2019)
Restriction site‐associated DNA sequencing (RADseq) has emerged as a useful tool in systematics and population genomics. A common feature of RADseq data sets is that they contain missing data that arise from multiple sources including genealogical sampling bias, assembly methodology and sequencing error. Many RADseq studies have demonstrated that allowing sites (single nucleotide polymorphisms, SNPs) with missing data can increase support for phylogenetic hypotheses. Two non‐mutually exclusive explanations for this observation are that (a) larger data sets contain more phylogenetic information; and (b) excluding missing data disproportionally removes sites with the highest mutation rates, causing the exclusion of characters that are likely variable and informative. Using a RADseq data set derived from the East African banana frog, Afrixalus fornasini (up to 1.1 million SNPs), we found that missing data thresholds were positively correlated with the proportion of parsimony‐informative sites and mean branch support. Using three proxies for estimating site‐specific rate, we found that the most conservative missing data strategies excluded rapidly evolving sites, with four‐state sites present only when allowing ≥60% missing data per SNP. Topological similarity among estimated phylogenies was highest for the data sets with ≥60% missing data per SNP. Our results suggest that several desirable phylogenetic qualities were observed when allowing ≥60% missing data per SNP. However, at the highest missing data thresholds (80% and 90% missing data per SNP), we observed differences in performance between high‐ and mixed‐weight DNA extraction samples, which may indicate there are trade‐offs to consider when using degraded genomic template with RADseq protocols.

Hierarchies of evolutionary radiation in the world’s most species rich vertebrate group, the Neotropical Pristimantis leaf litter frogs - Emily H. Waddell; Marco Crotti; Stephen C. Lougheed; David C. Cannatella; Kathryn R. Elmer (Systematics and Biodiversity, 2018)

Comments on detecting rogue taxa using RogueNaRok - Mark Wilkinson; Marco Crotti (Systematics and Biodiversity, 2017)

Diagnostic accuracy of two tests for determination of anti-m2 in the diagnosis of primary biliary cirrhosis: Is it possible to predict the course of the disease? - Antonio Maria Alfano; Alessandra Romito; Cristiana Marchese; Marco Battistini; Giliola Crotti; Arturo Ferrini; Cristina Mancinetti; Tilde Manetta; Giulio Mengozzi; Paola Merlach; Marco Migliardi; Maria Teresa Tambuzzo (Immunologic Research, 2017)

Asaia , a versatile acetic acid bacterial symbiont, capable of cross‐colonizing insects of phylogenetically distant genera and orders - Elena Crotti; Claudia Damiani; Massimo Pajoro; Elena Gonella; Aurora Rizzi; Irene Ricci; Ilaria Negri; Patrizia Scuppa; Paolo Rossi; Patrizia Ballarini; Noura Raddadi; Massimo Marzorati; et al. (Environmental Microbiology, 2009)
Summary Bacterial symbionts of insects have been proposed for blocking transmission of vector‐borne pathogens. However, in many vector models the ecology of symbionts and their capability of cross‐colonizing different hosts, an important feature in the symbiotic control approach, is poorly known. Here we show that the acetic acid bacterium Asaia , previously found in the malaria mosquito vector Anopheles stephensi , is also present in, and capable of cross‐colonizing other sugar‐feeding insects of phylogenetically distant genera and orders. PCR, real‐time PCR and in situ hybridization experiments showed Asaia in the body of the mosquito Aedes aegypti and the leafhopper Scaphoideus titanus , vectors of human viruses and a grapevine phytoplasma respectively. Cross‐colonization patterns of the body of Ae. aegypti , An. stephensi and S. titanus have been documented with Asaia strains isolated from An. stephensi or Ae. aegypti , and labelled with plasmid‐ or chromosome‐encoded fluorescent proteins (Gfp and DsRed respectively). Fluorescence and confocal microscopy showed that Asaia , administered with the sugar meal, efficiently colonized guts, male and female reproductive systems and the salivary glands. The ability in cross‐colonizing insects of phylogenetically distant orders indicated that Asaia adopts body invasion mechanisms independent from host‐specific biological characteristics. This versatility is an important property for the development of symbiont‐based control of different vector‐borne diseases.